2008
DOI: 10.1158/0008-5472.can-07-5175
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein–Mediated Resistance to Hsp90-Directed Therapy Is Eclipsed by the Heat Shock Response

Abstract: Despite studies that show the antitumor activity of Hsp90 inhibitors, such as geldanamycin (GA) and its derivative 17-allylamino-demethoxygeldanamycin (17-AAG), recent reports indicate that these inhibitors lack significant singleagent clinical activity. Resistance to Hsp90 inhibitors has been previously linked to expression of P-glycoprotein (P-gp) and the multidrug resistant (MDR) phenotype. However, the stress response induced by GA treatment can also cause resistance to Hsp90-targeted therapy. Therefore, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 50 publications
2
54
2
Order By: Relevance
“…18,32,29 It is important to emphasize that Hsp70 up-regulation results in resistance to Hsp90 inhibitors, not sensitization. 40,41 In our study Hsp70 was up-regulated after tanespimycin administration in blasts from 83% of patients. However, this Hsp70 up-regulation sometimes occurred before administration of tanespimycin (day 3, Figures 2B and 2D), possibly reflecting cytarabine-induced stress.…”
Section: Discussionmentioning
confidence: 49%
“…18,32,29 It is important to emphasize that Hsp70 up-regulation results in resistance to Hsp90 inhibitors, not sensitization. 40,41 In our study Hsp70 was up-regulated after tanespimycin administration in blasts from 83% of patients. However, this Hsp70 up-regulation sometimes occurred before administration of tanespimycin (day 3, Figures 2B and 2D), possibly reflecting cytarabine-induced stress.…”
Section: Discussionmentioning
confidence: 49%
“…The related quinone reductase NQO2 can also reduce 17AAG to 17AAGH 2 in cell-free studies using rhNQO2 and nicotinamide riboside (Siegel et al, 2007); however, at present there are no data in cellular systems demonstrating a role for NQO2 in the reduction of 17AAG. Other factors include the level of expression of drug transporters such as multi-drug resistance 1 and p-glycoprotein as well as the compensatory induction of heat shock proteins including Hsp27 and Hsp70, which all have been linked to resistance to 17AAG (McCollum et al, 2006(McCollum et al, , 2008Zhang et al, 2010). The role of Hsp90 oncogenic client proteins in stimulating cell proliferation is also an important determinant of tumor sensitivity to Hsp90 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…P-glycoprotein is known to be involved in cancer cell resistance to many chemotherapeutic agents [10]. Several studies have also shown that P-glycoprotein was involved in the resistance of tumor cells to geldanamycin or its derivatives [11,12].…”
Section: Introductionmentioning
confidence: 99%